A Conceptual Model of Predictors of SMEs’ Performance in Context of Sudan - Abdelrahman, Osman Elsheikh (2017)
Purpose: SMEs’ performance in Sudan is in the downturn and calls for research-based solution. To address it, this conceptual study proposes a model entailing management accounting practices (costing, budgeting, and performance measures practices) as predictors of SMEs’ performance. Also, research findings on the relationship between management accounting practices and performance are inconsistent, this study proposes a model entailing management accounting practices as determinants of SMEs’ performance with the moderating role of external business environment.Design/methodology/approach: This work is theorized based on extensive literature survey through which a conceptual model is developed and discussed.Inconsistent relationship between management accounting practices and performance is evaluated and established via published research. Also, moderating role of external business environment is discussed and validated based on the contingency theory.Findings: This paper proposes a conceptual model to serve as an answer to how Sudanese SMEs’ performance can be improved through management accounting practices.Research limitations/Implications: The proposed model in this work is based on survey of published research, but it can be empirically solidified further through collection and analysis of relevant data.Practical Implications: The paper can help SMEs’ owners/ managers and policy makers to understand how properly-adopted management accounting practices can improve SMEs’ performance.Originality/value: The proposed conceptual framework is an exceptional and all-inclusive model that will expectantly improve the relevant body of literature and serve as useful guide for stakeholders on how the performances of SMEs can be boosted to enable them catch up with the SMEs’ performance level of the developed countries in order to boost the economy of Sudan as a nation.